FITODEGRADASI DENGAN TANAMAN PACING (Speciosus Cheilocostus) UNTUK MENURUNKAN KANDUNGAN Pb, Cd Dan Hg LIMBAH CAIR LABORATORIUM - Trisnawati, Ni Nyoman; Manuaba, Ida Bagus Putra; Suprihatin, Iryanti Eka (CAKRA KIMIA (Indonesian E-Journal of Applied Chemistry); Vol 4 No 1 (2016), 2016)
ABSTRAK: UPT. Laboratorium Analitik Universitas Udayana menghasilkan limbah yang mengandung bahan-bahan kimia berbahaya. Sistem pengolahan air limbah yaitu fitodegradasi, menggunakan tanaman Pacing ( Cheilocostus speciosus ) telah dicoba untuk mengolah limbah cair laboratorium. Konstruksi unit pengolahan terdiri dari sebuah bak terbuat dari beton dengan media  tanah berukuran 7 m x 1,2 m x 0,34 m yang ditumbuhi Pacing. Penelitian dilakukan selama dua minggu meliputi penelitian eksperimental, observasi pre dan post perlakuan. Efektivitas sistem  fitoremediasi dalam menurunkan kandungan Hg adalah 100% pada hari ketiga, Cd sebesar 77,17 % dan Pb sebesar 9,50 % pada hari keempat. Kandungan Pb, Cd dan Hg berkurang secara signifikan setelah fitoremediasi.   ABSTRACT: UPT Analytical Laboratory of Udayana University produced liquid waste which contained dangerous chemicals such as : lead (Pb), Cadmium (Cd), and Mercury (Hg). Processing system of liquid waste using phytodegradation of pacing plant ( Cheilocostus specios us) has been studied to reduce the concentrations of heavy metals of laboratory liquid waste. The construction of the processing unit consisted of conerete tank filled with soil media grown over with pacing plant. The size of the tank was; 7 meters in length, 1.2 meters in width and 0.35 meters in depth. The duration  of the experiment was 2 weeks, by observation of pre and post treatment to record the effectivenesss of the pacing plants in reducing the concentrations of Pb, Cd and Hg in liquid waste. The results showed the effectiveness of the system in reducing the concentration of Pb, Cd and Hg were 9,50 %; 77,17 % and 100 % respectively.  The concentration of  Pb, Cd and Hg decreased significantly after treatment.
Keywords: Phytodegradation, Effectiveness, Pacing plant (Cheilocostus speciosus)